Assessment of inland flood hazard sensitivity to hydrological intensification in coastal watersheds - Miller, Robert L. (Frontiers in Water, 2022)
Intensification of the hydrologic cycle induced by climate variability and landscape modification is expected to increase the frequency of extreme flood events. Multi-jurisdictional approaches to manage inland flood risks at watershed scales demand the ability to objectively assess not only future flood potentials, but to also set priorities based upon multiple factors such as the stream channels most sensitive to hydrologic stress. This study presents a method to estimate flood hazard sensitivities to increasing stormwater runoff due to hydrologic intensification (e.g., urbanization, climate effects) on local and watershed scales. The method is demonstrated in the low-gradient inland watershed regions of southwestern coastal Louisiana, USA. Utilizing highly detailed numerical models from the Federal Emergency Management Agency (FEMA), absolute and relative flood sensitivities were calculated for 45 flood-prone stream channels in the Lafayette, LA region. Channel sensitivities to flood hazards induced by changes in the 10-yr (10% annual exceedance probability) flood flows were quantified by analysis of 485 scenarios developed using a downward counterfactual scaling strategy. Relying entirely upon publicly-available numerical models and input datasets, the study revealed key information about the relationship between estimable hydraulic characteristics (e.g., conveyance, resistance, and flow) and absolute and relative flood hazard sensitivity measures on a per-channel basis. Information from the subset of detailed numerical models was efficiently leveraged to provide a regional map of relative flood sensitivities. The methodology is robust and can be applied in very general settings to address the concern of hydrologic intensification in practical flood risk management applications.